2021
DOI: 10.3390/polym13020216
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Amphiphilic Copolymers of Dimethylamino Ethyl Methacrylate and Methyl Methacrylate to Control Biofilm Adhesion for Antifouling Applications

Abstract: Amphiphilic copolymers are recognized as important biomaterials and used as antibacterial agents due to their effective inhibition of bacterial growth. In current study, the amphiphilic copolymers of P(DMAEMA-co-MMA) were synthesized using free radical polymerization by varying the concentrations of hydrophilic monomer 2-dimethylamino ethylmethacrylate (DMAEMA) and hydrophobic monomer methyl methacrylate (MMA) having PDI value of 1.65–1.93. The DMAEMA monomer, through ternary amine with antibacterial property … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 55 publications
(61 reference statements)
4
27
0
Order By: Relevance
“…Traces of GPC distribution was unimodal symmetric that showed the uniformity of the copolymers via free‐radical polymerization. There was slight molecular weight distribution Mw/Mn, <1.4 of all copolymers 31 …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Traces of GPC distribution was unimodal symmetric that showed the uniformity of the copolymers via free‐radical polymerization. There was slight molecular weight distribution Mw/Mn, <1.4 of all copolymers 31 …”
Section: Resultsmentioning
confidence: 86%
“…32 This is due to the hydrophobic nature of MMA and the shorter chain of cationic hydrophilic monomer DMAEMA present in the structure of amphiphilic copolymers. 31 In these copolymers, P1 has a greater concentration of hydrophilic content, DMAEMA and has a lower contact angle 67 . In the case of P4 copolymer, the contact angle is 84 due to the greater concentration of hydrophobic content MMA.…”
Section: Wettability In Terms Of Contact Anglementioning
confidence: 99%
“…A review suggested that an ideal amphiphilic antimicrobial polymer bearing a cationic arm has low molecular weight, a low level of lipophilicity, and is biocompatible towards eukaryotic cells [ 24 ]. An amphiphilic copolymer, P(DMAEMA-co-MMA), as shown in Figure 4 , was successfully synthesized through the free radical polymerization of various concentrations of hydrophilic monomer 2-dimethylamino ethylmethacrylate (DMAEMA) and hydrophobic monomer methyl methacrylate (MMA) [ 58 ]. It was found that the copolymer with a high concentration of DMAEMA showed high biocidal activity against Gram-positive bacteria due to the presence of more amine groups along the DMAEMA chain.…”
Section: Classes Of Antimicrobial Materials For Antimicrobial Coatingmentioning
confidence: 99%
“…Most cationic polymers bear amine functions that can be protonated, such as polyethyleneimine (PEI), poly−L−(lysine) (PLL), chitosan, and poly [2−(N,N−dimethylamino)ethyl methacrylate] (PDMAEMA) [ 134 ]. While these polymers have inherent cationic charges, others have been developed by introducing cationic moieties such as aminated cellulose, which, compared to chitosan, represent a novel cationic cellulose derivative with improved mucoadhesive properties as well as sufficient hydration at physiological pH [ 135 ].…”
Section: Asas With Apsmentioning
confidence: 99%